Amperometric Tyrosinase Biosensor Based on Carbon Black Paste Electrode for Sensitive Detection of Catechol in Environmental Samples - Wong, Ademar [UNESP]; Santos, Anderson M.; Fatibello-Filho, Orlando; Sotomayor, Maria D. P. T. [UNESP] (Wiley, 2021)
In this work, a renewable tyrosinase-based biosensor was developed for the detection of catechol, using a carbon black paste electrode, without any mediator. The effect of pH, type of electrolyte, and amount of tyrosinase enzyme were explored for optimum analytical performance. The best-performing biosensor in amperometric experiments at potential −0.2 V vs. Ag/AgCl (3 mol L−1 KCl) was obtained using a 0.1 mol L−1 phosphate buffer solution (pH 7.0) as electrolyte. Under optimized conditions, the proposed biosensor had two concentration linear ranges from 5.0×10−9 to 4.8×10−8 and from 4.8×10−8 to 8.5×10−6 mol L−1 and a limit of detection of 1.5×10−9 mol L−1. The apparent Michaelis-Menten constant ((Formula presented.)) was calculated by the amperometric method, and the obtained value was 1.2×10−5 mol L−1 whose result was similar when compared with other studies previously. The biosensor was applied in river water samples, and the results were very satisfactory, with recoveries near 100 %. In addition, the response of this biosensor for different compounds, taking into account their molecular structures was investigated and the results obtained showed no interference with the response potential of catechol. The electrochemical biosensor developed in this work can be considered highly advantageous because it does not require the use of a mediator (direct detection) for electrochemical response, and also because it is based on a low-cost materials that can be used with success to immobilise other enzymes and/or biomolecules.
Keywords: carbon black; catechol; electrochemical biosensor; glutaraldehyde; tyrosinase enzyme